A critical literature review on reuse and recycling of construction waste in construction industry. (2021) - Janani, R.; Kaveri, V.
Abstract: Development squander material is a significant issues of development field. This paper says that, detailed study on literatures, list of materials used, reuse of materials, sources of wastes and the places where the materials can be reused. Finally, comparison of percentage on waste materials (Standard waste and Actual waste at site through interview), Table for the sources and reuse of waste as per literature study, suggestion have been given to reuse the waste and suggestion given to manage the materials.